1993
DOI: 10.1093/intimm/5.10.1239
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of cDNAs encoding a LD78 receptor and putative leukocyte chemotactic peptide receptors

Abstract: Several cDNA clones encoding receptors for leukocyte chemoattractants, including IL-8, C5a, N-formyl peptides (FP), and platelet-activating factor, have been isolated in the past 3 years. The primary structure of these receptors revealed that they are members of the superfamily of G protein-coupled receptors containing seven transmembrane domains. In this study the polymerase chain reaction was carried out to isolate novel cDNA clones encoding human receptors of IL-8 related cytokines, chemokines, from a human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(81 citation statements)
references
References 0 publications
4
77
0
Order By: Relevance
“…the ALX receptor [22,27,39]. ALX was cloned from a human monocyte cDNA library [40]. In ALX-transfected CHO cells, which were tested for binding of LXB4, LTD4, LTB4 and PGE2, only LTD 4 showed competition with LXA 4 binding [22].…”
Section: Discussionmentioning
confidence: 99%
“…the ALX receptor [22,27,39]. ALX was cloned from a human monocyte cDNA library [40]. In ALX-transfected CHO cells, which were tested for binding of LXB4, LTD4, LTB4 and PGE2, only LTD 4 showed competition with LXA 4 binding [22].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, microarray results showed that IL-10 increased mRNA levels of adhesion/migration-related genes such as L-selectin, VEGF receptor-1, t-PA, HM74, formyl peptide receptor-1 and lipoxin A4 receptor (Figure 3). The last three genes are involved in the synthesis of peptide receptors [38][39][40] that mediates leukocyte chemotaxis by binding peptides derived from protein degrada- tion occurring in damaged/diseased areas. 41 The overexpression of these receptors might play an important role in NK cell migration in response to the liberation of danger signals (eg peptides) freed in the tumor microenvironment.…”
Section: Genementioning
confidence: 99%
“…On the other hand, the ability of SDF-1 to interact with neutrophils and the expression of CXCR4 on their cell surface is controversial. Although two studies demonstrated that neutrophils expressed significant amounts of CXCR4 mRNA [12,13], more recent evidence from a functional study [11], and results using flow cytometry [14], have indicated lack of CXCR4 on neutrophils. Third, SDF-1 is constitutively expressed [15,16], whereas other chemokines are released on stimulation with pro-inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%